MENINGKATKAN PEMAHAMAN ANAK DALAM MENGURUS JENAZAH DENGAN METODE DEMONSTRASI DI KELAS X-AGAMA MAN KOTA MOJOKERTO SEMESTER GANJIL TAHUN PELAJARAN 2018/2019 - Inayati, Dwi Imanora (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2018)
The learning process is basically a process of communication between teacher and student and can be said to be successful if students achieve the expected competence, because it is a reflection of students' ability to master a material that is inseparable from the teacher's ability to choose and use appropriate and effective strategies. The application of the demonstration method will be able to provide a more meaningful learning experience for students. Students are able to learn directly and discover their own learning experiences by doing hands-on practice. The application of this method is also very useful because it has advantages including to overcome the limitations of language in exposure to the material, provide more skills for students through learning experiences, and focus student attention on the learning process. This study aims: 1) Describe the activities of teachers in learning to improve children's understanding in managing bodies with demonstration methods in class X-RELIGION MAN Mojokerto City. 2) Describe the activities of students in learning activities to improve children's understanding in taking care of the body with a demonstration method in class X-RELIGION MAN Mojokerto City. 3) Describe learning with demonstration methods in improving children's understanding in managing bodies in Class X-RELIGION MAN Mojokerto City. This research is a classroom action research conducted in collaboration. The design of the problem situation, and the ways for collaboration with children, are the main focus of the meeting that takes place between the teacher and researcher. This research was conducted at MAN Mojokerto with the address Jl. Cinde Baru VIII Kec. Warrior Kulon Mojokerto 61326 (0321) 390742 Kota Mojokerto. The subjects of this study were 39 students of Class X-AGAMA. The study was conducted in odd semester 2018/2019 academic year, for 3 months (July, August, September 2018). The cyclical action research procedures are: 1) planning, 2) implementation, 3) observation, and 4) reflection, through a series of cycles. Data collection through Observation (Observing), Artifacts and Documents (Testing) and Non-Standardized Tests. Testing Instrument items with validity test, reliability test, Calibration test (Difficulty Level) and Distinguishing Power test. the entire data analysis process is interactive using the Miles and Huberman model with the final mix method analysis. The results of the study concluded: 1) Teacher activity has increased in Pre-Action to get results 62.86 percent and increased in Cycle I by 75 percent and increased in Cycle II by 87.86 percent; 2) Student activity has increased in Pre-Action to get 42.86 percent results and increased in Cycle I by 65 percent and increased in Cycle II by 86.43 percent; 3) The average value of the test (Classical Absorption) has increased in Pre-Action to get 68.97 percent results and increased in Cycle I by 77.43 percent and increased in Cycle II by 85.89 percent. Classical Learning Completion has increased in Pre-Action obtained a result of 61.54 percent and increased in Cycle I by 69.23 percent and increased in Cycle II by 87.18 percent.